PENGARUH SISTEM KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI GRAHA MANDIRI TASPEN BARABAI - Putri Sri Noor Rezeki; Syahrial Shaddiq; Khuzaini; Zakky Zamrudi (Jurnal Riset Multidisiplin Edukasi, 2026)
The objectives of this study are to examine and analyze: 1) to determine the influence of work systems on employee performance at Graha Mandiri Taspen Barabai. 2) to determine the influence of compensation on employee performance at Graha Mandiri Taspen Barabai. This study used a quantitative descriptive research method. The population in this study were 28 Bank Mandiri Barabai employees. The sample in this study consisted of 28 employees, using total sampling. The data analysis technique used multiple linear regression. Based on the results of this study, the results indicate that 1) the work system influences employee performance at Graha Mandiri Taspen Barabai. 2) Compensation influences employee performance at Graha Mandiri Taspen Barabai. 3) Work systems and compensation influence employee performance at Graha Mandiri Taspen Barabai